Encephalitozoon cuniculi Infection in Rabbits (Oryctolagus cuniculus): Data from an International Survey of Exotic and Small Animal Veterinarians - Fabiano Montiani-Ferreira; Anja Joachim; Frank Künzel; Franz Riegler Mello; Emma Keeble; Jennifer Graham; Jaume Martorell; Jean-Francois Quinton; Ann Gottenger; Carolyn Cray (Animals)
In 2022–2023, the first survey of clinicians regarding Encephalitozoon cuniculi infection of rabbits was undertaken. The purpose was to assess the current worldwide knowledge of clinicians regarding influence of breed and age, clinical presentations, use of various diagnostic tools, and treatment regimens and to explore how responses may differ by geographic location. Identifying mostly as exotic animal clinicians, 339 respondents participated, with nearly half from the United States and the remainder from 35 other countries. Neurological signs were most consistently reported as associated with Encephalitozoon cuniculi and the most recurrent clinical case presentation. Other responses showed differences by geographic location. For example, age predilection for disease varied, with 71.1% of international respondents indicating that infection was more common in young rabbits versus 28.9% who suggested it was more frequent in older rabbits. This was significantly different (p = 0.001) from the information from respondents from the United States, where 48.0% indicated that younger rabbits had an increased incidence versus 52.0% who indicated that older age increased occurrence. While some differences may be related to the practice composition and the training level of respondents, many responses were in alignment with the existing literature. Future inquiries should focus more on these discrepancies to aid in generating guidelines for the diagnosis and treatment of this infectious disease.